2017
DOI: 10.1080/1360080x.2017.1377966
|View full text |Cite
|
Sign up to set email alerts
|

Equity in higher education and graduate labour market outcomes in Australia

Abstract: The rate of higher education participation in Australia has increased over the past decade for individuals from disadvantaged backgrounds. This study contributes to the knowledge on the outcomes of disadvantaged individuals who complete higher education by looking at the labour market outcomes of university graduates from equity groups. The number of Indigenous graduates and graduates with disabilities was found to be very low, suggesting that more needs to be done to improve higher education completion for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…For example, Hout (1988Hout ( , 1994 found no significant differences in occupational status among higher-education graduates from different social classes in the US. In Australia, Li et al (2017) found also no significant differences between low-and high-SEB graduates in the probability of being employed in a high-quality job and earnings. However, we also found support for Hypothesis 2, based on social and cultural capital, effectively-maintained-inequality and life-course theories.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Hout (1988Hout ( , 1994 found no significant differences in occupational status among higher-education graduates from different social classes in the US. In Australia, Li et al (2017) found also no significant differences between low-and high-SEB graduates in the probability of being employed in a high-quality job and earnings. However, we also found support for Hypothesis 2, based on social and cultural capital, effectively-maintained-inequality and life-course theories.…”
Section: Discussionmentioning
confidence: 70%
“…Equity can be achieved through affording all students access to excellent educational resources and teachers who can build academic learning inside and outside the classrooms ( Sleeter, 2008 ). In Australia, there is a need to study ways of enhancing equity among students ( Li et al., 2017 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Meanwhile, the local pool of young tertiary graduates in Australia has continued to expand in the past two decades (ABS 2008;Li and Miller 2013b;Kemp and Norton 2014;Harvey 2016), as also documented for other industrialised nations (Capsada-Munsech 2017;Li et al 2018). Initiatives such as the FEE-HELP loan scheme, the Higher Education Participation and Partnerships programme and the Widening Participation agenda were introduced to promote access to higher education, mainly amongst students who come from a disadvantaged background (Harvey 2016;Li et al 2017). In 2012, Australia further replaced a supply-driven education system that limited the number of university enrolments with a demand-driven framework to allocate funding based on student demand (Kemp and Norton 2014).…”
Section: A Weakening Labour Market For Recent Tertiary Graduatesmentioning
confidence: 99%
“…Further, the rising percentage of non-native English-speakers suggests potential declines in the English language proficiency of international graduates, which have been identified as one of the main factors contributing to their poor labour market outcomes in Australia (Birrell 2006a;Birrell and Edwards 2007;Birrell and Healy 2008;Arkoudis et al 2009;Hawthorne 2010Hawthorne , 2014Robertson et al 2011;Hawthorne and To 2014;Arber and Rahimi 2015). Further, non-native English-speaking graduates are vulnerable to discrimination and prejudicial treatment in the Australian labour market, as documented amongst Australians coming from a non-English-speaking background (Birrell and Hawthorne 1999;Ho and Alcorso 2004;Hawthorne 2005;Kler 2006;Green et al 2007;Chiswick and Miller 2010;Massey and Parr 2012;Tan and Lester 2012;Li and Miller 2015;Li et al 2017).…”
Section: The Changing Profile Of International Graduate Population In Australiamentioning
confidence: 99%
See 1 more Smart Citation